2012
DOI: 10.4067/s0716-97602012000100001
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of environmental pollutants to male infertily: A working model of germ cell apoptosis induced by plasticizers

Abstract: Bisphenol A [2,2-bis(4-hydroxyphenyl)propane] (BPA), 4-nonylphenol (NP) and di(2-ethylhexyl)phthalate (DEHP), and its metabolite mono-2-ethylhexyl phthalate (MEHP) are chemicals found in plastics, which act as endocrine disruptors (EDs) in animals, including human. EDs act like hormones in the endocrine system, and disrupt the physiologic function of endogenous hormones. Most people are exposed to different endocrine disruptors and concern has been raised about their true effect on reproductive organs. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 139 publications
0
52
0
Order By: Relevance
“…Our results showed that BPA exposure activated the Fas/FasL pathway. Once the Fas system is activated, the effector caspase, caspase-3 will be cleaved and subsequently activated, which finally commits cells into apoptosis [31]. Our data showed that the mRNA expression of caspase-3 was increased, and even the protein expression of cleaved caspase-3 was also enhanced.…”
Section: Discussionmentioning
confidence: 80%
“…Our results showed that BPA exposure activated the Fas/FasL pathway. Once the Fas system is activated, the effector caspase, caspase-3 will be cleaved and subsequently activated, which finally commits cells into apoptosis [31]. Our data showed that the mRNA expression of caspase-3 was increased, and even the protein expression of cleaved caspase-3 was also enhanced.…”
Section: Discussionmentioning
confidence: 80%
“…Germ cells at different stages possess unique physiological features [31] and respond differently to exogenous stimuli, apoptosis of germ cell can be induced by exposure to chemicals agents [1].…”
Section: Discussionmentioning
confidence: 99%
“…Spermatogenic cells are highly sensitive to physical and chemical environmental factors. In the past decades, studies had reported that some environmental factors are associated with deleterious effects on spermatogenesis [1]. For example, bisphenol A exposure at an environmentally relevant dose induces meiotic abnormalities in adult male rats [2]; bis-(2-ethylhexyl) phthalate (DEHP) impaired spermatogenesis in zebrafish by inducing a mitotic arrest of germ cells [3]; fenvalerate, a widely used pyrethroid insecticide, induces germ cell apoptosis in mouse testis through the Fas/FasL signaling pathway [4].…”
Section: Introductionmentioning
confidence: 99%
“…Human beings are mainly exposed to BPA via dietary ingestion of leachings from the inner lining of cans and microwave containers during heating of food materials of through beverages in polycarbonate bottles due to repeated usage or contact with acid/alkaline (Biles et al, 1997;Jeng, 2014). It has been valued that the human body is exposed to concentrations of 10 μg/day of BPA and it can be detected in several human body samples, such as serum, urine, amniotic fluid of pregnant women, breast milk and even in semen (Inoue et al, 2002;Calafat et al, 2005;Carlsen et al, 2005;EC-SCF, 2006;Phillips and Tanphaichitr, 2008;Lagos-Cabré and Moreno, 2012). BPA quantification in amniotic fluid and in umbilical cord reported a mean level around 1 ng/ml (Fenichel et al, 2012;N'Tumba-Byn et al, 2012).…”
Section: Bpa and Alkyphenols Bispenol Amentioning
confidence: 97%